Clinical and ultrasonographic findings of the digital flexor tendons and ligaments of the metacarpal/metatarsal region in gaited horses - Schade J. (2021)
© 2021 Hippiatrika Verlagsgesellschaf. All rights reserved.Summary: The breed can influence the characteristics of tendon and ligament injuries; however, they have not been evaluated in gaited horses. This study aimed to evaluate the clinical and ultrasonographic findings of tendons and ligaments of the palmar/plantar metacarpal and metatarsal region in gaited horses. Ninety-nine adult gaited horses not in training were evaluated, of which 51 were of the Mangalarga Marchador (MM) and 48 of the Campeiro breeds. Clinical exam of the locomotor system was performed in all animals and real-time ultrasonography evaluation when specific alterations in the tendons and ligaments were identified. Clinical changes were evidenced in 22.22 % of the animals, 11.11 % in the MM and 11.11 % in the Campeiro horses. Fifty-three alterations were observed, which involved the superficial digital flexor tendon (9.43 %), deep digital flexor tendon (1.89 %), accessory ligament of the deep digital flexor tendon (26.42 %), lateral branch of the suspensory ligament (16.98 %), medial branch of the suspensory ligament (18.87 %) and digital sheath (26.42 %). Horses above 12 years of age and with previous participation in competitions were associated with a risk of 4.64 and 3.75 times greater for the development of injuries, respectively. Changes in tendons and ligaments of the metacarpal and metatarsal region are frequent in gaited horses and occur in a similar way in both breeds. Tendinopathies and desmopathies are present in unused gaited horses. Therefore, the return to activity should be preceded by a complete evaluation of the palmar and plantar structures of the metacarpal and metatarsal region.